Assessment of dredging impact on hydrodynamics of Surma River using hydrodynamic model: HEC-RAS approach - Pritam Karmakar Rony; Md. Misbah Uddin; Gazi Md. Riasat Amin; Dr Gulam Md. Munna; Dheeman Das Dibya (Water Practice and Technology, 2023)
Surma River is the main source of fresh water in the South-Eastern region of Bangladesh. Every year, huge amounts of sediment loads are coming from upstream, which are settling down on the Surma River bed, hindering the safe passage of flow that contributes to the change in the hydrodynamic of the river. Recently, dredging has been done in the Sunamganj area to increase the navigability of the river. In this study, the hydrodynamics of the Surma River has been investigated to check the impact of dredging with the help of HEC-RAS. Flood frequency analyses have been done for 5, 10, 25, 50, and 100 years return periods, and a comparison of water level, velocity, and discharge has been done before and after dredging. Before dredging the water level, the flow path was very high, and velocity was low, but after dredging the water level, the flow path decreases and velocity increased. Discharge also decreases after dredging in the six stations, which are located in the dredged area, and the values are 1,375.41, 1,374.31, 1,373.73, 1,369.7, 1,373.11, and 1,372.08 m3/s. Before dredging, the values are 1,669.62, 1,665.53, 1,664.69, 1,658.12, 1,624.23, and 1,383.98 m3/s. HIGHLIGHTS Dredging causes huge funding. If it is not done in the proper place, then it is a wastage of money. My research focuses on the assessment of dredging.; Many researchers have done 1D modeling of the Surma River. But the impact assessment of dredging has not been done earlier.; This model is very innovative by which exact dredging location can be found, and its impact can be analyzed and the predication of flood can also be determined.;